Uso problemático de videojuegos y rendimiento académico en una institución pública de Huancavelica - Rojas De La Cruz, Paúl (2023)
The intelligent use of new technologies is very beneficial, especially in times of pandemic; one of its main advantages is that it helps minimize time and shorten distances. However, due to the confinement, it is evident that children and teenagers who play video games have intensified their addiction, and even those who did not play have increased their gaming hours. The objective was to establish the relationship between video game addiction and academic performance among fifth-grade students at the National College of Sciences and Arts. The methodology used was a quantitative approach, with a descriptive method and a correlational descriptive design. The sample consisted of 60 students. The Spearman's Rho coefficient was used for hypothesis testing. The results showed that in terms of video game addiction, 55% were in the mild level, 30% in the severe level, and 15% in the moderate level. In terms of academic performance, 76.7% of students were in the beginning level, and 23.3% were in the process level. In conclusion, a medium and significant negative relationship was established between video game addiction and academic performance among fifth-grade students at La Victoria de Ayacucho - Huancavelica College in 2022.